Beyond Chronology: Integrating Local History and Digital Storytelling to Foster Civic Virtues and National Identity in High School Students - Burhanuddin, Burhanuddin (LPPM Universitas PGRI Sumatera Barat, 2024)
This qualitative research examines the integration of local history and digital storytelling as pedagogical strategies to foster civic virtues and strengthen national identity among high school students in Indonesia. Employing thematic analysis of data collected through semi-structured interviews (n=42), focus group discussions (n=6), and classroom observations (n=24 sessions), the study investigated how these complementary approaches influence students' understanding of civic responsibilities, emotional connections to national heritage, and commitments to social participation. Findings revealed three interconnected themes: (1) local history as a bridge between individual identity and national consciousness, (2) digital storytelling as a mechanism for affective engagement and critical consciousness development, and (3) the collaborative learning environment as a catalyst for internalized civic virtues. Students demonstrated enhanced comprehension of how local contributions shaped national narratives, developed stronger emotional attachments to national identity, and expressed greater willingness to participate in civic activities. The study contributes to contemporary civic education discourse by demonstrating that when local historical narratives are mediated through digital storytelling practices, students develop more nuanced, emotionally resonant understandings of national identity and civic responsibility, transcending chronological fact-retention toward meaningful civic engagement.